2022
DOI: 10.1007/s11250-022-03205-8
|View full text |Cite
|
Sign up to set email alerts
|

Emerging infectious diseases may spread across pig trade networks in Thailand once introduced: a network analysis approach

Abstract: In Thailand, pork is one of the most consumed meats nationwide. Pig farming is hence an important business in the country. However, 95% of the farms were considered smallholders raising only 50 pigs or less. With limited budgets and resources, the biosecurity level in these farms is relatively low. Pig movements have been previously identified as a risk factor in the spread of infectious diseases. Therefore, the present study aimed to explicitly analyze the pig movement network structure and assess its vulnera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…As previously observed, animal movements can spread infection over long distances (17). Travel restrictions at the local, regional, and national levels are often among the first control policies enforced once a disease outbreak occurs (37).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As previously observed, animal movements can spread infection over long distances (17). Travel restrictions at the local, regional, and national levels are often among the first control policies enforced once a disease outbreak occurs (37).…”
Section: Discussionmentioning
confidence: 92%
“…Social network analysis (SNA) has previously been used to describe how different livestock species are moved and traded in Thailand, including cattle ( 15 ), goats ( 16 ), pigs ( 17 ), and chickens ( 18 ). SNA can quantify the structure and geographical distribution of poultry trade networks in Thailand, helping policymakers direct resources to areas at the highest risk of AI transmission.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative explanation of plasmid sharing in multiple farms could be the movement of people and animals between farms colonized with these bacteria and/or plasmids, as observed for other microorganisms [66][67][68]. A recent study highlighting the Thai pig trade network indicated that this network could facilitate the spread of infectious diseases [69].…”
Section: Discussionmentioning
confidence: 99%